Control of rot in Capsicum pubescens: Evaluation of defense inducers under in Vitro conditions, Acobamba 2024 - Chavez, Victor (2024)
The productiototalitym pubescens is caused by the pathogen Fusarium sp, the objective of the research was to determine precisely how the use of defense inducers affects the control of the causal agent of fruit rot of Capsicum pubescens in Acobamba, the research was applied in an explanatory level; A Completely Randomized Design (CRD) was used with 17 treatments and 4 replications, to identify Fusarium sp as the causal agent of fruit rot, the vegetative material was placed in humid chambers to accelerate the manifestation of the sign, the purification of the pathogen was carried out by hyphal tip seeding; the pathogen presented an average radial growth of 9 cm² in a period of 7 days, the formation of fusiform macroconidia was observed; the treatment with silicon using the commercial product Silicofarm at a dose of 15.5 and 31 ml per liter inhibited in its totality the growth of the mycelium of Fusarium sp in vitro, so it is advisable to apply it in plantations in production of Capsicum pubescens.